Nutrient niche specificity for glycosaminoglycans is reflected in polysaccharide utilization locus architecture of gut Bacteroides species - Overbeeke, Annelieke; Hausmann, Bela; Nikolov, Georgi; Pereira, Fatima C.; Herbold, Craig W.; Berry, David (Frontiers in Microbiology, 2022)
Introduction Glycosaminoglycans (GAGs) present in the mucosal layer can be used as nutrients by certain intestinal bacteria, particularly members of the Bacteroides. GAG abundances are altered in some diseases such as inflammatory bowel diseases, which may affect microbial composition and activity, and it is therefore important to understand GAG utilization by members of the gut microbiota. Methods We used growth assays, transcriptomics, and comparative genomics to evaluate chondroitin sulfate (CS) and hyaluronan (HA) degradation ability by multiple gut Bacteroides species. Results and discussion We found that not all Bacteroides species able to degrade CS could also degrade HA, despite having lyases which act on both compounds. We propose that in the model organism Bacteroides thetaiotaomicron, the lyase BT_3328 in combination with surface binding proteins BT_3329 and BT_3330 and potentially BT_4411 are involved in HA breakdown. Furthermore, degradation of both compounds provides public goods for other Bacteroides, including non-degraders, suggesting that cooperative degradation as well as cross-feeding may be widespread in the mucosal glycan utilization clade.